2020
DOI: 10.1039/c9lc01128e
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic label-free bioprocessing of human reticulocytes from erythroid culture

Abstract: Developments in Dean flow fractionation (DFF) and deterministic lateral displacement (DLD) for label-free purification of cultured RBCs from human hematopoietic stem cells. An advancement in sorting and closed-loop manufacturing of viable human RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
(80 reference statements)
0
16
0
Order By: Relevance
“…In 2020, Guzniczak et al demonstrated a two-stage separation process consisting first of a microfluidic chamber that employs deformability-based RBC sorting followed by a membrane filtration step for an overall cell purity of 99% in the final product [ 179 ]. In the same year, Zeming and colleagues investigated both Dean Flow Filtration (DFF) and Deterministic Lateral Displacement (DLD) sorting using a microfluidic approach and demonstrated that both methods were capable of achieving higher cell recovery over traditional fluorescence cell sorting [ 180 ]. Studies such as these are vital towards the development of clinically relevant bioprocesses, not just for blood production, but for many other systems with cellular products.…”
Section: Generating Clinically Suitable Ipsc-rbcs For Transfusionmentioning
confidence: 99%
“…In 2020, Guzniczak et al demonstrated a two-stage separation process consisting first of a microfluidic chamber that employs deformability-based RBC sorting followed by a membrane filtration step for an overall cell purity of 99% in the final product [ 179 ]. In the same year, Zeming and colleagues investigated both Dean Flow Filtration (DFF) and Deterministic Lateral Displacement (DLD) sorting using a microfluidic approach and demonstrated that both methods were capable of achieving higher cell recovery over traditional fluorescence cell sorting [ 180 ]. Studies such as these are vital towards the development of clinically relevant bioprocesses, not just for blood production, but for many other systems with cellular products.…”
Section: Generating Clinically Suitable Ipsc-rbcs For Transfusionmentioning
confidence: 99%
“…More experimental approaches include lab-on-a-chip microfluidic label-free reticulocyte-sorting methods. 66 All these possibilities need testing and optimizing on a large culture scale which is expensive, therefore, highlighting filtration as a key area of research calling for innovation as well as commercial investment and collaboration.…”
Section: Reticulocyte Filtration and Storagementioning
confidence: 99%
“…They found that the positions of the streamlines were in good agreement with the experimental results and were able to use the computer model to aid in their microfluidic chip design. Research has also been carried out on other methods of cell separation, such as separation by cell rigidity [53]. Regarding studies on malaria, there are, again, only a few examples that were implemented in COMSOL.…”
Section: Simulationsmentioning
confidence: 99%
“…There is a wide range of methods for simulating microfluidics using a variety of software. One of the more popular and used software is COMSOL Multiphysics version 5.5 (COMSOL, Boston, MA, USA) with the microfluidics add-on module [52][53][54][55].…”
Section: Simulationsmentioning
confidence: 99%